Energy stored and output during a volleyball attack jump for different skill levels of female performers - Hsieh, C. T. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of the current study was to investigate the mechanical energy stored and output during a volleyball attack jump for different skill levels of female players. Five female skilled volleyball players and five recreational female volleyball players were recruited. Each participant performed five maximum regular 4-step attack jumps on two Kistler force platforms with conjunction of 3D motion analysis. Results indicated that there was no significant difference of energy stored between the two groups of performers. The mechanical energy output of the competitive group was significantly greater than the recreational group. Finally, the energy stored, output, and CoM downward displacement were statistically associated with jump height in skilled group and only energy returned was a significant variable that associated with jump height in non-skilled group (P <.01).